Manure studies in the Ethiopian highlands. I. Effect on Medicago sativa L. grown on an alfisol - Saka, A.R.; Haque, I. (International Livestock Centre for Africa, 1993)
An alfalfa field experiment was conducted at the Debre Zeit Experiment station for a period of 2 years with the main objective of investigating the effects of cattle manure om dry matter yields, plant tissue nutrient concentration and plant nutrient uptake. Dry matter yields were significantly increased by manure application. Plant tissue nutrient concentration data indicated that these were generally not significantly influenced by manure application, except for a few harvesting times, where P and Mg were significantly increased. Plant nutrient uptake was generally significantly increased by the addition of manure, except for N, Ca and Mg, which were not significantly increased. However, uptake of all nutrient elements was significantly correlated with increasing manure rates. The uptake of large quantities of nutrient by alfalfa indicates the potential of this legume to provide high quality feed for livestock and, if returned to the soil, for soil fertility improvement. The correaltion between dry matter yields and plant tissue nutrient concentration were generally poor, except for K and Mg during the last harvest. The result indiactes that small changes in nutrient concentration would result in large variations in predicted dry matter yields and that alfalfa can successfully be grown at Debre Zeit.